Law, Development, and the Rights of Chinese Women: A Snapshot from the Field - Woo, Margaret Y. K. (Columbia Journal of Asian Law, 2005)
In this era of post-communist regimes, several trends pervade academic and economic development debates. First, market principles are said to be not only the prime weapon for invigorating stagnant economies, but also the route to greater freedoms and liberties. Certainly, the embrace of the market has given an amazing boost to China’s national economy, now growing at an enviable annual rate of about 7%. Yet the broad application of market concepts has also brought about serious domestic problems, from widening gaps between rich and poor to massive urban migration, widespread unemployment, corruption, and growing unrest in both city and countryside. The meaning of market concepts to the rights of Chinese citizens thus requires a more complex understanding of what kind of rights are at issue and for to whom those rights flow. Hand in hand with market development has marched a second trend: the reliance on legal structures and the language of rights. Legal development, critical to market development, has assumed prominence not only as a means of effecting economic and political change, but also as an end in itself-as a goal synonymous with the liberal norms of freedom and democracy. Rule of law in World Trade Organization- parlance and in the international human rights framework refers to a system that features independent and impartial decision-makers, transparent and open rules that apply uniformly to all, and a process that ensures the protection of fundamental rights and interests. This approach suggests that, as a matter of course, contracts should be privately negotiated and enforced according to law. By extension, disadvantaged groups should also seek to vindicate their rights in the courts rather than in the streets. Where the Chinese state previously loomed in the provision of health and other social welfare benefits, private individuals are now responsible for the negotiation of such benefits with each other, and seek enforcement within the parameters of the legal structure.